Nilai-Nilai Budaya Lokal dan Kekerasan terhadap Perempuan Masa Hamil di Kabupaten Donggala, Sulawesi Tengah - Rosmala Nur (Humaniora, 2012)
Domestic violence during pregnancy and post-childbirth is a serious problem faced by women, because each year the form and quality are increasingly complex and its prevalence is increasing. This research aims to analyze factors of local cultural values and religious causes of violence during pregnancy-post-childbirth. This research has been conducted in Sunju Village (rural) and Tanjung Batu Village (urban) Donggala regency, Central Celebes. The samples were all married women of childbearing age who are pregnant, women at post-childbirth, those who have experienced pregnancy and giving birth at maximum of two years ago, and experienced violence at that time. The respondents were 94 women. The data were collected through structured interviews, indepth interviews, observation moderate participation, focus group discussion and documentation. The results showed that husband to wife violence occurred during pregnancy and post-childbirth. Higher experience of violence was suffered by women in urban area than those in the rural. The percentage of violence toward wife in the urban reached 43,28 percent, while that in the rural was 42,8 percent. The values of local culture, that is culture siri ', naeya, marital money/doi' balanca and religious values can trigger that husband to wife violence during pregnancy-post-childbirth in urban and rural area.